1991
DOI: 10.1111/j.1532-5415.1991.tb05898.x
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Fluid Administration in Elderly Subjects: Validation of an Under‐Used Technique

Abstract: In a crossover study in six volunteers over the age of 65, absorption of 500 mL of normal saline given subcutaneously was compared with that given intravenously. Tritiated water and technetium pertechnetate were used as water tracers. Tritium radioisotope levels in the blood increased in a smooth curve during subcutaneous infusion, reaching equilibrium levels within 60 minutes. The area under the curve after subcutaneous infusion was almost identical to that after intravenous infusion in all subjects. Radioact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
3

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 9 publications
0
39
0
3
Order By: Relevance
“…Sehen and SingerEdelstein [1] reviewed 1,850 s.c. infusions given to 270 patients in acute and long-stay geriatric beds and concluded that the s.c. route was the method of choice for adminis tering fluid to elderly patients in nonurgent situations. Other writers have reported simi lar findings [2][3][4], Lipschitz et al [7] demon strated using radioisotope tracers that normal saline (with hyaluronidase) given subcuta neously was rapidly and fully absorbed into the bloodstream.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Sehen and SingerEdelstein [1] reviewed 1,850 s.c. infusions given to 270 patients in acute and long-stay geriatric beds and concluded that the s.c. route was the method of choice for adminis tering fluid to elderly patients in nonurgent situations. Other writers have reported simi lar findings [2][3][4], Lipschitz et al [7] demon strated using radioisotope tracers that normal saline (with hyaluronidase) given subcuta neously was rapidly and fully absorbed into the bloodstream.…”
Section: Discussionmentioning
confidence: 92%
“…For the purpose of this study, we used a continuous infusion over 24 h. Overnight infusions leave the pa tient free from restrictions by day and are par ticularly useful in patients requiring rehabili tation [4], Hyaluronidase, which breaks down s.c. tissue, increases the speed of absorption of s.c. fluids [2,7], but is not necessary in most patients.…”
Section: Discussionmentioning
confidence: 99%
“…10,23,[39][40][41][42] Clinical history demonstrates the increased dispersion and faster absorption of a broad range of drugs and fluids administered with hyaluronidase products. 10,23,[38][39][40][41][42][43][44] With rHuPH20, for example, Thomas and colleagues 45,46 have demonstrated an accelerated PK profile of SC morphine coadministered with rHuPH20 compared with SC morphine alone, with earlier and greater peak exposure and comparable total bioavailability. Similarly, administration of rHuPH20 significantly enhanced gravity-driven SC infusion flow rates of fluid and electrolytes compared with placebo, leading the authors to suggest the possibility of using hyaluronidaseenabled SC infusions as replacements for pump-driven intravenous fluid therapy.…”
Section: History Of Hyaluronidase Administrationmentioning
confidence: 99%
“…Hyaluronidase is known to improve diffusion of a solution of NaCl in the subcutaneous tissue and to decrease the delay of appearance of Na in plasma (11). In the presence of hyaluronidase, the appearance in plasma of tritiated water infused subcutaneously is as rapid as appearance following IV infusion (12). The same effect has not been demonstrated for glucose infusion.…”
Section: Discussionmentioning
confidence: 99%